Isolation of Ceratocystis-inhibiting bacteria in Acacia mangium - Jeffrey Chan, Natasha Deanna Chan (2018)
Acacia mangium is an important plantation species, especially for pulp and paper production, as well as wood composite products. Several pathogen species have been proven to be extremely detrimental to this species in the last 20 years, namely Ceratocystis sp., which is fatal in juvenile trees. The aim of this study is to isolate endophyte bacteria in healthy A. mangium trees, and to test these isolated endophyte bacteria species against Ceratocystis sp. Bacteria exhibiting positive inhibiting abilities would be helpful as a means of future biological control to restore A. mangium plantations against it. The roots and leaves of Acacia mangium seedlings and trees were sterilized and cultured on 1% Nutrient Agar medium to culture endophyte bacteria. Each bacteria sample obtained was tested against Ceratocystis sp. on 1% Potato Dextrose Agar medium. Endophyte bacteria which possessed Ceratocystis-inhibiting abilities were successfully isolated, derived mostly from primary root of healthy Acacia mangium seedlings. In a total of 50 endophytic bacteria samples, ten endophytic bacteria samples possessing Ceratocystis-inhibiting abilities were successfully isolated.